Seismo-ionospheric coupling of two shallow and moderate earthquakes in Indonesia in 2024 observed via TEC analysis - Paudel, Madhu Sudan; Ghimire, Basu Dev; Chapagain, Narayan Prasad (BIBECHANA, 2026)
This research work aimed to investigate the seismo-ionospheric coupling during two 6.4 magnitude (M6.4) earthquakes occurred in Indonesia in 2024; one on March 22, near Paciran, Indonesia (latitude, longitude: 5.87° S, 112.36° E), and another on April 9, near Tobelo, Indonesia (at latitude, longitude: 2.698° N,127.06° E). We use the data from GNSS permanent ground stations BNOA and BTNG, available on the website of UNAVCO, to study the temporal variation of the ionospheric Total Electron Content (TEC) before and after the earthquake. Moreover, the spatiotemporal variation of the TEC is studied using the GIM-TEC map. We used a running-quartile-based method to estimate the upper bound (UB) and lower bound (LB) on TEC in order to identify the anomalies in the ionospheric TEC. The space weather condition during the time frame of both earthquakes is also examined in order to segregate the anomalies associated with geomagnetic disturbed and quiet days. Since the epicenter of both earthquakes belongs to the low-latitude region, the TEC anomalies could be observed over region including both crests of the Equatorial Ionospheric Anomaly (EIA). The difference of TEC (dTEC) with monthly running-median is estimated to study spatiotemporal variation of anomaly. The dTEC map shows the simultaneous negative and positive anomalies in magnetically conjugate regions in the crest of the EIA region from 6 days before the Paciran and from 11 days before the Tobelo earthquake. The negative anomaly on TEC is also observed to be associated with the morphological changes in the EIA curve. The physical mechanism behind the observed positive and negative anomalies is explained on the basis of the theory of radioactive radon emanation before the earthquake.